Optimal timing of influenza vaccine during pregnancy: A systematic review and meta‐analysis. Issue 5 (5th June 2019) - Cuningham, Will; Geard, Nicholas; Fielding, James E.; Braat, Sabine; Madhi, Shabir A.; Nunes, Marta C.; Christian, Lisa M.; Lin, Shin‐Yu; Lee, Chien‐Nan; Yamaguchi, Koushi; Bisgaard, Hans; Chawes, Bo; et al.
Abstract: Background: Pregnant women have an elevated risk of illness and hospitalisation from influenza. Pregnant women are recommended to be prioritised for influenza vaccination during any stage of pregnancy. The risk of seasonal influenza varies substantially throughout the year in temperate climates; however, there is limited knowledge of how vaccination timing during pregnancy impacts the benefits received by the mother and foetus. Objectives: To compare antenatal vaccination timing with regard to influenza vaccine immunogenicity during pregnancy and transplacental transfer to their newborns. Methods: Studies were eligible for inclusion if immunogenicity to influenza vaccine was evaluated in women stratified by trimester of pregnancy. Haemagglutination inhibition (HI) titres, stratified by trimester of vaccination, had to be measured at either pre‐vaccination and within one month post‐vaccination, post‐vaccination and at delivery in the mother, or in cord/newborn blood. Authors searched PubMed, Scopus, Web of Science and EMBASE databases from inception until June 2016 and authors of identified studies were contacted for additional data. Extracted data were tabulated and summarised via random‐effect meta‐analyses and qualitative methods. Results: Sixteen studies met the inclusion criteria. Meta‐analyses found that compared with women vaccinated in an earlier trimester, those vaccinated in a later trimester had a greater fold increase in HI titres (1.33‐ to 1.96‐fold) and higher HI titres in cord/newborn blood (1.21‐ to 1.64‐fold). Conclusions: This review provides comparative analysis of the effect of vaccination timing on maternal immunogenicity and protection of the infant that is informative and relevant to current vaccine scheduling for pregnant women.